Eros in the Hamsunian Male Figure: Fantasy Women in Knut Hamsun’s 1890s Literature - Yamasaki, Lisa (Nordlit, 2020)
Using a psychoanalytic perspective, I explore Knut Hamsun’s novels, Sult (1890), Mysterier (1892), Pan (1894), and Victoria (1898) and focus on the power that the women in fantasy have over the different male protagonists, whom I term the Hamsunian male. Within each fantasy, the women either dominate or exert supernatural power over the Hamsunian male. By undertaking such an investigation, I examine how the desired women in fantasy differ from the main female characters, in so far as they portray the Hamsunian male’s desire that ranges from intense eroticism to fear and death. While my focus on the female characters in the Hamsunian male differs from the discussions concerning the main female characters, I note that such women comment on the depiction of the masculine gender in Hamsun’s work. Furthermore, the discussion shows the power of women in fantasy, thus questioning whether they should continue to be disregarded as only superficially feminine.